The Rate and Molecular Spectrum of Spontaneous Mutations in the GC-Rich Multichromosome Genome of Burkholderia cenocepacia. Issue 3 (12th May 2015) - Dillon, Marcus M; Sung, Way; Lynch, Michael; Cooper, Vaughn S
Abstract: Spontaneous mutations are ultimately essential for evolutionary change and are also the root cause of many diseases. However, until recently, both biological and technical barriers have prevented detailed analyses of mutation profiles, constraining our understanding of the mutation process to a few model organisms and leaving major gaps in our understanding of the role of genome content and structure on mutation. Here, we present a genome-wide view of the molecular mutation spectrum in Burkholderia cenocepacia, a clinically relevant pathogen with high %GC content and multiple chromosomes. We find that B. cenocepacia has low genome-wide mutation rates with insertion–deletion mutations biased toward deletions, consistent with the idea that deletion pressure reduces prokaryotic genome sizes. Unlike prior studies of other organisms, mutations in B. cenocepacia are not AT biased, which suggests that at least some genomes with high %GC content experience unusual base-substitution mutation pressure. Importantly, we also observe variation in both the rates and spectra of mutations among chromosomes and elevated G:C > T:A transversions in late-replicating regions. Thus, although some patterns of mutation appear to be highly conserved across cellular life, others vary between species and even between chromosomes of the same species, potentially influencing the evolution of nucleotide composition and genome architecture.